CAUSES OF PNEUMONIA IN CHILDREN - Akbarova Muruvvat Sobirovna (Scholar Express Journals, 2025)
Pneumonia in children is one of the leading causes of childhood mortality in the global health system, especially in developing countries. This article provides a scientific overview of the causes of pneumonia, providing an indepth analysis of infectious (viruses, bacteria, fungi) and non-infectious (environmental factors, aspiration, chronic diseases) etiological factors. Particular attention is paid to the distribution of pathogens by age group, epidemiological studies (for example, the PERCH project) and preventive measures. The article emphasizes the dominance of viral infections (RSV, rhinovirus, etc.) and the role of bacterial causes (Streptococcus pneumoniae, Haemophilus influenzae), and also shows the importance of molecular diagnostics and vaccination. As a result, recommendations are made to improve strategies for the prevention and treatment of pneumonia.
Keywords: Pneumonia in children; etiology; viral infections